2018
DOI: 10.1152/ajprenal.00364.2017
|View full text |Cite
|
Sign up to set email alerts
|

ATP induces PAD4 in renal proximal tubule cells via P2X7 receptor activation to exacerbate ischemic AKI

Abstract: We previously demonstrated that renal tubular peptidylarginine deiminase-4 (PAD4) is induced after ischemia-reperfusion (IR) injury and this induction of PAD4 exacerbates ischemic acute kidney injury (AKI) by promoting renal tubular inflammation and neutrophil infiltration. However, the mechanisms of renal tubular PAD4 induction after IR remain unknown. Here, we tested the hypothesis that ATP, a proinflammatory danger-associated molecular pattern (DAMP) ligand released from necrotic cells after IR injury, indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…17 Few studies have examined the importance of P2 receptors in AKI; however, inhibition of P2X7R attenuates inflammation and IRI. 18,19 Overall, ATP is implicated in several physiologic and pathologic settings in the kidney.…”
mentioning
confidence: 99%
“…17 Few studies have examined the importance of P2 receptors in AKI; however, inhibition of P2X7R attenuates inflammation and IRI. 18,19 Overall, ATP is implicated in several physiologic and pathologic settings in the kidney.…”
mentioning
confidence: 99%
“…Renal IR injury induces protein and mRNA, as well as activity of renal tubular PAD4, and pharmacological inhibition or gene deletion of PAD4 protects kidney from renal IR injury by reducing inflammatory response and apoptosis [80,81]. In additional studies, we demonstrated that ATP induces renal tubular PAD4 via protein kinase C signaling, and PAD4 is the critical mediator of P 2 X 7 -mediated kidney inflammation and injury after renal IR injury because the P 2 X 7 receptor failed to exacerbate ischemic AKI in PAD4 knockout mice [82]. Furthermore, we found that PAD4 preferentially citrullinates inhibitor of κB (IκB) kinase-γ (IKK-γ, also known as NFκB essential modulator or NEMO) over other IKK subunits, IKK-α or IKK-β.…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
“…Inhibition of purinergic receptors was protective in both ischemic and sepsis-induced AKI (111,112). ATP and selective agonists of the P2X 7 receptor were shown to activate peptidyl arginine deaminase 4 (PAD4) in proximal tubular cells (PTCs) and exacerbate IRI (113). Recently, the P2X 4 receptor was shown to exacerbate ischemic AKI through NLRP3 inflammasome signaling in the renal proximal convoluted tubules (PCTs) (114).…”
Section: Mitochondrial Alarminsmentioning
confidence: 99%